Improving the Quality of Quranic Reading through the An-Nahdliyah Method - Aqiel, Hilmi Wildan; Umar, Muallief (STAI Miftahul Ula Nganjuk, 2023)
This study addresses the challenge of Quranic education in contemporary times, particularly the difficulty encountered by many Muslim children and adolescents in mastering Quranic reading. The research focuses on three main objectives: (1) assessing the average quality of Quranic reading among students at TPQ Al-Ikhlas Klinter Pelem Kertosono, Nganjuk; (2) evaluating the implementation of the An-Nahdliyah method in enhancing Quranic reading skills; and (3) identifying the supporting and hindering factors in the application of this method. A qualitative approach was employed, involving observation, interviews, and documentation, with data analyzed using descriptive qualitative techniques. The findings reveal that while the overall Quranic reading quality among students is good, there are still some students with poor proficiency, necessitating specialized instruction. The An-Nahdliyah method has been effective in improving reading skills, with the method's rhythmic approach aiding in quicker comprehension. Supporting factors include student motivation, teacher competence, and family environment, while challenges include student apathy, lack of discipline among teachers, and insufficient family support